India's mass-market clean mobility initiatives and its unique, customized business models for light electric vehicles - Mohua Mukherjee (The Oxford Institute for Energy Studies, 2022)
Around 99 per cent of vehicles running on India's roads are powered by internal combustion engines running on fossil fuels (petrol, diesel, and some CNG). The passenger car is still a largely aspirational product for around one hundred million newly middle-class Indians (20 million families). Given the current, still very low per capita car ownership in India of 22 per 1,000 citizens, compared to 980 in the US and 850 in the UK, it is an opportune time for India to embrace alternative sustainable mobility solutions for a green and prosperous future. This can only succeed if accessible and affordable solutions are available in adequate numbers. Also, given the segmented nature of the market and the different dynamics within each segment, government support could be better targeted. This effort has already started with the proposed interoperable and standardized light-vehicle battery, to promote greater affordability in the battery-swapping segment. Also, government incentives for increased localization of battery assembly, and eventually cell manufacturing, as well as continued public support for R&D to explore alternative battery chemistries, will all help to reduce costs. The real challenge for India lies in E2Ws and E3Ws, used by nearly 1 billion people in the country every day. Converting these vehicles to electric, making them affordable and convenient, and doing what it takes to turn E2Ws and E3Ws into the first preference over ICE vehicles when making a purchase decision, is what India should be supported and measured on. In India, the adoption of e-mobility through the individual purchase of EVs is not likely to happen very fast in the mass segment of the market, (180 million families or 900 million people) even for 2Ws with leased batteries, selling at a price point today of under 1,000. It is likely to require a few more years until battery prices come down to around half of what they are today. The important lesson for EV market players in India is that the cash flow patterns of the mass market segment, such as for example a delivery driver's daily or monthly income, do not allow the owner to pay the 800 battery cost upfront in addition to buying the body of the EV for another 800. Even the battery leasing option, amounting to an estimated 87 per month for a gig worker, is a financial stretch. This is extremely important in a low-income consumer market where high-cost products such as lithium-ion EV batteries are supposed to be adopted by consumers who are struggling financially. Despite the billions that the government has set aside to lower the upfront cost of entry, it appears that the product may still be out of reach for most of the budget market, until the battery costs and battery leasing costs fall further. India's ongoing attempts to standardize a subset of swappable batteries for the light-vehicle segment, to make them interoperable across multiple vehicle brands, are likely to increase affordability and create market confidence, as one type of battery becomes 'commoditized'.
Keywords: 330; batteries; battery swapping; electric mobility; electricity vehicles; India; Transport